Tri-element nanozyme PtCuSe as an ingenious cascade catalytic machine for the amelioration of Parkinson’s disease-like symptoms - Xu, Hongdang; Ding, Xin; Li, Lingrui; Li, Qing; Li, Zhiye; Lin, Hongqi (Frontiers in Bioengineering and Biotechnology, 2023)
Parkinson’s disease (PD), as the second most common neurodegenerative disease after Alzheimer’s, has become intractable with the increasing aging global population. The exploration of nanomedicine has broadened the opportunities for developing novel neuroprotective therapies. In particular, polymetallic functional nanomaterials have been widely used in the biomedicine field in recent years, exhibiting flexible and diversified functions and controllable properties. In this study, a tri-element nanozyme (PtCuSe nanozyme) has been developed with desirable CAT- and SOD-like activities for the cascade scavenging of reactive oxygen species (ROS). In particular, the nanozyme is suitable for relieving nerve cell damage by removing reactive oxygen species in cells and mitigating the behavioral and pathological symptoms in animal models of Parkinson’s disease. Therefore, this ingenious tri-element nanozyme may have potential in the treatment of Parkinson’s disease and other neurodegenerative diseases.